OPTIMIZATION OF PONTOON 35 ILIR PIER FACILITIES AT THE PALEMBANG CITY TRANSPORTATION OFFICE - Syarifudin, Achmad; Rizki Hidayat, M. Noor; Mulyati, Ely; Rosyad, Farlin (Ensiklopedia of Journal, 2024)
The dock is one of the parts used to carry out the activities of arrival and departure of ships, boarding and disembarking of passengers and loading and unloading of goods. The role of the pier is very important to support these activities. To support the smooth running of these activities, the dock used must be in good condition so that the activities of arriving and departing ships, boarding and unloading passengers and loading and unloading of goods can run smoothly. However, the condition of the Pontoon Pier infrastructure at the Palembang City Transportation Department needs attention, especially from the management, in this case the Palembang City Transportation Department, because at low tide it runs aground and the condition of the floating type pier is leaking and flooded, resulting in the pier tilting and the pier being too overhanging. to land so that Palembang City Transportation Service ships which have a high draft cannot dock and unload at the pier because they are not safe, smooth and comfortable for service users. However, the condition of the Pontoon Pier infrastructure at the Palembang City Transportation Department needs attention, especially from the management, in this case the Palembang City Transportation Department, because at low tide it runs aground and the condition of the floating type pier is leaking and flooded, resulting in the pier tilting and the pier being too overhanging. to land so that Palembang City Transportation Service ships which have a high draft cannot dock and unload at the pier because they are not safe, smooth and comfortable for service users.Keywords: Pontoon Pier, Optimization, Loading and Unloading